Miti e leggende sulla riforma degli ordinamenti universitari: il caso dell'offerta formativa in Italia - Franco Bagnoli; Vanna Boffo; Pietro Causarano; Filippo Visintin (Firenze University Press, 2010)
This research work started in a small university group that it is part of a bigger organisation named Coordinamento Ricercatori Università di Firenze. In Italy, the Universty System is changing after new laws from July 2008 and Januray 2009. As researchers and assistant professors, the authors try reflecting about the sweeping changing of the Italian University Sistem from a scientific and methodological point of view.